Curcumin Represses NLRP3 Inflammasome Activation via TLR4/MyD88/NF-κB and P2X7R Signaling in PMA-Induced Macrophages - Kong, Fanqi; Ye, Bozhi; Cao, Jiatian; Cai, Xueli; Lin, Lu; Huang, Shanjun; Huang, Weijian; Huang, Zhouqing (Frontiers in Pharmacology, 2016)
Abstract Aims: In the NOD-like receptor (NLR) family, the pyrin domain containing 3 (NLRP3) inflammasome is closely related to the progression of atherosclerosis. This study aimed to assess the effects of curcumin on NLRP3 inflammasome in phorbol 12-myristate 13-acetate (PMA)-induced macrophages and explore its underlying mechanism. Methods: Human monocytic THP-1 cells were pretreated with curcumin for 1 h and subsequently induced with PMA for 48 h. Total protein was collected for Western blot analysis. Cytokine interleukin (IL)-1β release and nuclear factor kappa B (NF-κB) p65 translocation were detected by ELISA assay and cellular NF-κB translocation kit, respectively. Results: Curcumin significantly reduced the expression of NLRP3 and cleavage of caspase-1 and IL-1β secretion in PMA-induced macrophages. Moreover, Bay (a NF-κB inhibitor) treatment considerably suppressed the expression of NLRP3 inflammasome in PMA-induced THP-1 cells. Curcumin also markedly inhibited the upregulation of toll-like receptor 4 (TLR4), myeloid differentiation factor 88 (MyD88), phosphorylation level of IκB-α, and activation of NF-κB in PMA-induced macrophages. In addition, purinergic 2X7 receptor (P2X7R) siRNA was administered, and it significantly decreased NLRP3 inflammasome expression in PMA-induced macrophages. Furthermore, curcumin reversed PMA-stimulated P2X7R activation, which further reduced the expression of NLRP3 and cleavage of caspase-1 and IL-1β secretion. Silencing of P2X7R using siRNA also suppressed the activation of NF-κB pathway in PMA-induced macrophages, but P2X7R-silenced cells did not significantly decrease the expression of TLR4 and MyD88. Conclusions: Curcumin inhibited NLRP3 inflammasome through suppressing TLR4/MyD88/NF-κB and P2X7R pathways in PMA-induced macrophages.